#SB40 Side event: Advancing readiness to fast-track climate-smart agriculture in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
This side event took place at the UNFCCC 40th Session of the Subsidiary Bodies (SB40) and was organized by CCAFS East Africa. To fast-track early action on Climate-Smart Agriculture (CSA), countries need to address readiness for CSA, transform their policies and strengthen institutions to ensure food security and enhance livelihoods of smallholder farmers. Photos: P. Høj (CCAFS)